The impacts of situational impairment on touch gestures in public spaces: Walking in sunlight. (June 2020) - Hosseini, Masoumehsadat; Hamidi, Hamid Reza; Kermanshahani, Shokoh
Abstract: In recent years, the use of touchscreen mobile devices in a variety of places and contexts has been raised. Specific interaction context induced impairment and disabilities that can limit the usage of these devices. For instance, the use of a mobile device while walking in sunlight limits the visual attention and results in performance reduction. In this paper, we present a study that investigates distinctions between the made gestures by individuals in two different situations: while walking in sunlight glare and sitting at a table without visibility impairment. The results show that (1) the individuals tend to draw larger and broader gestures in situational impairment, (2) the variation in the time and speed depended on the user familiarity with the gestures, and (3) there wasn't great different behavior in how to apply strokes.